Does It Matter If Students (Dis)like School? Associations Between School Liking, Teacher and School Connectedness, and Exclusionary Discipline - Graham, Linda J.; Gillett-Swan, Jenna; Killingly, Callula; Van Bergen, Penny (Frontiers in Psychology, 2022)
School liking is an important factor in student engagement, well-being, and academic achievement, but one which is also potentially influenced by factors external to the individual, such as school culture, teacher support, and approaches to discipline. The present study employed survey methodology to investigate associations between school liking and disliking, teacher and school connectedness, and experiences of exclusionary discipline from the perspective of students themselves. Participants included 1,002 students (Grades 7-10) from three secondary schools serving disadvantaged communities. Results indicated clear differences between students who like and dislike school in terms of their preferred school activities and school disciplinary history, with students who disliked school experiencing overall lower school connectedness. Moreover, students who disliked school experienced less positive relationships with their teachers, and this was even more pronounced for students who had been previously suspended. The findings reveal key differences between students who do and don’t like school; differences that may be masked by typical research approaches. This research indicates the need for more nuanced, student-informed approaches to inclusive school reform.